Atypical STAT5B deficiency, severe short stature and mild immunodeficiency associated with a novel homozygous STAT5B Variant. (1st January 2023) - Catli, Gonul; Gao, Wen; Foley, Corinne; Özyilmaz, Berk; Edeer, Neslihan; Diniz, Gulden; Losekoot, Monique; van Doorn, Jaap; Dauber, Andrew; Dundar, Bumin N.; Wit, Jan M.; Hwa, Vivian
Abstract: STAT5B deficiency, a rare autosomal recessive disorder characterized by severe growth hormone insensitivity (GHI) and immunodeficiency, can manifest as fatal pulmonary complications. We describe atypical STAT5B deficiency associated with a novel homozygous frame-shift STAT5B variant [ c.1453delG, p.(Asp485Thrfs*29)] identified in a young 17.6 yr old female subject who had severe postnatal growth impairment, biochemistries typical of GHI, an immune profile notable for hypergammaglobulinaemia and elevated B lymphocytes, and lack of pulmonary disease. Marked elevation of serum prolactin and pathologically diagnosed eczema were evident. In reconstitution studies, the STAT5B p.(Asp485Thrfs*29) was expressed although expression was reduced compared to wild-type STAT5B and a previously identified STAT5B p.(Gln368Profs*9) variant. Both truncated STAT5B peptides could not be activated by GH, nor mobilize to the nucleus. We conclude that an intact, functional, STAT5B is essential for normal GH-mediated growth, while expressed loss-of-function STAT5B variants may alleviate severe immune and pulmonary issues normally associated with STAT5B deficiency. Highlights: A new pathological, loss-of-function, recessive frameshift STAT5B variant was identified. The expressed truncated STAT5B variant is unresponsive to GH. Intact, functional, STAT5B is essential for GH-mediated growth. Expressed, loss-of-function, STAT5B variants can be associated with mild immune dysfunction.